Panorámica del comportamiento de la movilidad intermunicipal en la provincia de Cienfuegos. / Overview of the behavior of internal migrations in the province of Cienfuegos. - Yanili García Ramos (Novedades en Población, 2021)
This work shows a brief overview of the inter-municipal mobility in the municipalities of the province of Cienfuegos at the municipal level in 2016, based on the migration databases available in the National Office of Statistics and Information. With this information, indicators are calculated that evaluate the level, age and sex structure of inter-municipal mobility. In addition, the migration efficiency index is calculated to measure the effects on the redistribution of the population within the municipalities. The results indicate that the Cienfuegos municipality, as the provincial capital, is ratified as the main recipient of the population from other municipalities. There is a bigger presence of women as protagonists of inter-municipal mobility, as well as a high participation of the 15-29 and 30-59 age groups. / RESUMEN El presente trabajo muestra una breve panorámica del comportamiento de la movilidad intermunicipal en los municipios de la provincia de Cienfuegos a escala municipal en el año 2016, a partir de las bases de datos de migración disponibles en la Oficina Nacional de Estadísticas e Información. Con esta información se calculan indicadores que evalúan el nivel, la estructura de edad y sexo de la movilidad intermunicipal. Además, se calcula el índice de eficacia migratoria para medir los efectos que esta produce en la redistribución de la población al interior de los municipios. Los resultados apuntan a que el municipio Cienfuegos, por ser la capital provincial, se ratifica como principal receptor de población proveniente de otros municipios. Hay una mayor presencia de mujeres como protagonistas de la movilidad intermunicipal, así como una elevada participación de los grupos de 15 a 29 y 30 a 59 años.